2021
DOI: 10.3390/jpm11121281
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Antioxidant Enzymes with the Concentration of Fatty Acids in the Blood of Men with Coronary Artery Atherosclerosis

Abstract: Objective: To identify associations of fatty acids (FAs) with the antioxidant enzymes in the blood of men with coronary atherosclerosis and ischemic heart disease (IHD). Methods: The study included 80 patients: control group—20 men without IHD, the core group—60 men with IHD. The core group was divided into subgroups: subgroup A—with the presence of vulnerable atherosclerotic plaques, subgroup B—with the absence of vulnerable atherosclerotic plaques. We analyzed the levels of FAs, free radicals, superoxide dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Similarly, OA is a common monounsaturated FA that induces a cytotoxic response called "lipotoxicity," regulated by increased ROS levels or oxidative stress. An animal study showed that OA can lead to increased H 2 O 2 levels, which are closely related to AS progression [46]. DHA is a major component of the phospholipid membrane and participates in membrane fuidity and signal transduction [47].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, OA is a common monounsaturated FA that induces a cytotoxic response called "lipotoxicity," regulated by increased ROS levels or oxidative stress. An animal study showed that OA can lead to increased H 2 O 2 levels, which are closely related to AS progression [46]. DHA is a major component of the phospholipid membrane and participates in membrane fuidity and signal transduction [47].…”
Section: Discussionmentioning
confidence: 99%
“…Reduced GSH Atherosclerosis, arterial aging lower GSH is a predictor of intima/media thickness [270,271] Hypertension ↑ GSH increased glutathione-related antioxidant defense in treated hypertensives [272] CAD ↓ in angiographically proven CAD [240] SOD activity Arterial aging negatively correlated with systolic and diastolic blood pressure, low serum SOD activity is an independent predictor of carotid intima/media thickening [ ↑ in men with IHD [242] GPx activity Atherosclerosis ↓ in prevalent atherosclerosis and lower values are associated with an increased risk of future cardiovascular events [275] Hypertension lower levels associated with high blood pressure in black women [276] IHD ↓ in men with IHD [242] any cardiovascular events lower GPx is associated with a higher risk of CV events [277] MDA Atherosclerosis, arterial aging ↑ with carotid intima/media thickening [271]…”
Section: Biomarker CV Disease Finding Referencementioning
confidence: 99%
“…The wide literature on oxidative stress in cardiovascular diseases (including reports on human and animal studies) also shows increased oxidant and decreased antioxidant activity in various disease conditions, including hypertension, atherosclerosis, vascular aging, ischemic heart, and cerebral diseases [ 39 , 55 , 57 , 74 , 75 , 77 , 212 ]. Interestingly, in atherosclerotic conditions, several studies have shown increased antioxidant activity using blood markers, which may show the compensatory upregulation of antioxidant defense mechanisms in this condition [ 240 , 241 , 242 ]. The findings of selected representative studies are summarized in Table 2 .…”
Section: Biomarkers Of Oxidative Stress In Copd and Cardiovascular Di...mentioning
confidence: 99%
“…This Special Issue on “Atherosclerosis: Technologies of Personalized Medicine” includes a review and ten original studies about epidemiologic, genetic aspects of atherosclerosis, antioxidant system, biomarkers of atherosclerosis. Four of the special-issue articles, Metelskaya et al [ 1 ], Gruzdeva et al [ 2 ], Shramko et al [ 3 ], Polonskaya et al [ 4 ], focus on the various biomarkers of atherosclerosis. Metelskaya et al [ 1 ] evaluated the feasibility of a combination of biochemical and imaging parameters for estimation of risk and severity of coronary atherosclerosis (CA), and to verify the created integrated biomarker (i-BIO) on the independent cohort.…”
mentioning
confidence: 99%
“…The authors revealed the pathogenetic significance of alterations in the adipokine and cytokine status of adipocytes of epicardial (EAT) and perivascular (PVAT) in patients with CAD. Shramko et al [ 3 ] researched associations of fatty acids (FAs) with the antioxidant enzymes in the blood of men with coronary atherosclerosis and ischemic heart disease (IHD). The study included 80 patients: control group—20 men without IHD, the core group—60 men with IHD.…”
mentioning
confidence: 99%